Fundamentals, misvaluation, and investment: The real story - Robert S. Chirinko; Huntley Schaller (Institute for Advanced Studies (IHS), 2006)
Is real investment fully determined by fundamentals or is it sometimes affected by stock market misvaluation? We introduce three new tests that: measure the reaction of investment to sales shocks for firms that may be overvalued; use Fama-MacBeth regressions to determine whether overinvestment affects subsequent returns; and analyze the time path of the marginal product of capital in reaction to fundamental and misvaluation shocks. Besides these qualitative tests, we introduce a measure of misvaluation into standard investment equations to estimate the quantitative effect of misvaluation on investment. Overall, the evidence suggests that both fundamental and misvaluation shocks affect investment.
Keywords: E44; E22; E32; G3; 330; investment; stock market; fundamentals; misvaluation; bubbles; real effects of financial markets